Detection of Renal Hypoxia in Lupus Nephritis Using Blood Oxygen Level-Dependent MR Imaging: A Multiple Correspondence Analysis - Huilan Shi; Tiekun Yan; Dong Li; Junya Jia; Wenya Shang; Li Wei; Zhenfeng Zheng (Karger Publishers, 2017)
Background/Aims: Nephrologists have pursued ideal, dynamic and noninvasive methods for assessing renal function and disease progression. Blood oxygen level dependent (BOLD) imaging is a useful technique for assessing renal disease. This current study was performed to explore the correlation between the hypoxia iconographical index and renal pathological features in lupus nephritis. Methods: Adult patients with lupus nephritis (LN) and healthy volunteers were recruited for this study. Renal biopsy tissues were characterized based on the LNISN/RPS 2003 classification. R2* values of functional magnetic resonance parameters were acquired using the BOLD technique. The data characteristics of R2* values of different pathological patterns were calculated. Multiple correspondence analysis (MCA) was performed to explore the correlation between R2* values and clinical or pathological features. Results: A total of twenty-three patients and eighteen healthy volunteers were examined with BOLD MRI. Renal pathological patterns included five class III (including 3 class III+V), eight class IV (including 4 class IV+V) and five class IV. The mean renal R2* values in LN patients were higher than those in healthy volunteers. R2* values in class V patients were higher than those in class IV and class III. The MCA showed that higher R2* values were associated with pathological features in class V patients. Conclusions: The extent of renal hypoxia in patients with LN was more serious compared with the healthy volunteers. Differentiated mechanisms of renal oxygenation are possibly involved in proliferative and non-proliferative LN patients. R2* values may be linked with multiple clinical and pathological indexes.